Análise da cadeia de suprimentos no pomar de produção da laranja e tangerina na Comunidade de São Pedro de Veneza no Município de Benjamin Constant, Amazonas - Noronha, Thiago Freitas (Brasil, 2024)
The present study entitled “Analysis of the Supply Chain in the Orange and Tangerine Production Orchard in the Community of São Pedro De Veneza in the Municipality of Benjamin Constant, Amazonas” aimed to analyze the activities of the supply chain of citrus fruits Orange Pêra and Tangerine Mimosa, produced in the community of São Pedro de Veneza in the Municipality of Benjamin Constant, in the State of Amazonas. The focus was on exploratory and descriptive research, with objective interviews to identify the obstacles and strengths of each link in the production chain, from the purchase of production support materials to marketing to the final consumer. The results point out that the activities that result in the value margin are directly related to the operational process of the production of citrus fruits, which implies the techniques of production and management of the fruits in an adequate way, thus reducing losses. Another link to be highlighted is the entire logistical process from the productive orchard to the producer's market, with technological development in the application of locomotion techniques, obtaining product quality and a longer period of durability in the market. And so does the activity to support human resource management, developing production in family farming. Therefore, nowadays the production performance has reduced significantly, resulting in the loss of orange and tangerine trees.